Increased Contribution of Extended Vegetation Growing Season to Boreal Terrestrial Ecosystem GPP Enhancement - Meng Yu; Yunfeng Cao; Jiaxin Tian; Boyu Ren (Remote Sensing)
Rapid Arctic warming is driving significant changes in boreal vegetation phenology and productivity. The potentially asynchronous response of these processes could substantially alter the relative impacts of phenological shifts on variations in gross primary productivity (GPP), but this remains poorly understood. The objective of this study is to quantify the impact of phenology extension on boreal ecosystem GPP changes across different periods from 1982 to 2018. To achieve this, we developed a statistical model that integrates vegetation phenology and physiology, and introduced a new metric, the Relative Increment Effect (RIE), to assess the contribution of phenology extension to GPP increase. Our analysis revealed that phenology extension became the dominant driver of GPP increment over time. Specifically, the overall RIE for boreal vegetation increased by 22% from the earlier period (P1: 1982–2000, 3.2) to the more recent period (P2: 2001–2018, 3.93). This increase was more pronounced for grass and shrub ecosystems. Spatial patterns showed that RIE increases were particularly concentrated at high latitudes, especially in northern Siberia. These findings suggested that phenology extension was playing an increasing role in regulating boreal ecosystem productivity, with significant implications for the boreal carbon budget under future warming scenarios.